Systematic Review : Kajian Literatur Sistematik Tentang Strategi Peningkatan Daya Saing Rumah Sakit di Era JKN - Purwadhi Purwadhi; Yani Restiani Widjaja; Liya Suwarni; Made putri widyantini (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is a systematic review aimed at identifying and analyzing hospital management innovation in the context of the National Health Insurance (JKN) system. By examining 20 recent journals published between 2019 and 2025, this research provides an overview of the key strategies that hospitals employ to enhance their competitiveness and improve service delivery. The focus includes management strategies, marketing approaches, operational efficiency, and the role of information technology. The analysis reveals that effective hospital management in the JKN era requires a combination of long-term strategic planning and short-term tactical adjustments to adapt to regulatory changes. A key element of success is visionary leadership that fosters a culture of innovation and emphasizes data-driven decision-making. Marketing strategies, which traditionally relied on word-of-mouth and local advertising, have significantly shifted toward digital marketing using social media and online platforms. This transformation helps hospitals expand their reach, engage with a broader audience, and retain patients through targeted campaigns.Operational efficiency is another critical factor. The implementation of Lean Management principles, service process innovations, and optimization of Hospital Management Information Systems (SIMRS) have contributed to significant improvements in hospital performance. Additionally, human resource management practices have evolved to focus on skill development and creating a workforce that can navigate the challenges posed by JKN. Furthermore, digital technology has revolutionized patient data management and enables real-time performance monitoring, allowing hospitals to maintain high-quality service standards. The study recommends that hospitals integrate management, marketing, and operational efficiency strategies, all supported by technology and a well-trained workforce. By doing so, hospitals can optimize their capabilities and enhance their service quality, ensuring better outcomes for both patients and the healthcare sector as a whole.